Glucose 6-phosphate transport in fibroblast microsomes from glycogen storage disease type 1b patients: evidence for multiple glucose 6-phosphate transport systems. - Leuzzi, R (2001)
In liver endoplasmic reticulum the intralumenal glucose-6-phosphatase activity requires the operation of a glucose 6-phosphate transporter (G6PT1). Mutations in the gene encoding G6PT1 cause glycogen storage disease type 1b, which is characterized by a loss of glucose-6-phosphatase activity and impaired glucose homoeostasis. We describe a novel glucose 6-phosphate (G6P) transport activity in microsomes from human fibroblasts and HeLa cells. This transport activity is unrelated to G6PT1 since: (i) it was similar in microsomes of skin fibroblasts from glycogen storage disease type 1b patients homozygous for mutations of the G6PT1 gene, and in microsomes from human control subjects; (ii) it was insensitive to the G6PT1 inhibitor chlorogenic acid; and (iii) it was equally active towards G6P and glucose 1-phosphate, whereas G6PT1 is highly selective for G6P. Taken together, our results provide evidence for the presence of multiple transporters for G6P (and other hexose phosphoesters) in the endoplasmic reticulum.